The Effect of Population Density, Educational Access Inequality and Health Access Inequality on Economic Growth - Ady Soejoto; M A Ghofur; Lucky Rachmawati (STAI Hubbulwathan Duri, 2022)
The public welfare is related to population growth and the availability of public goods such as education and health. Workforce with good welfare is expected to generate high labor productivity, so it can produce more output of goods and services and increase economic growth. Population density, educational access inequality, and health access inequality will have a negative effect on economic growth. The aimed of this study: First, to analyze the picture of economic growth, population density, educational access inequality, and health access inequality in Indonesia. Second, to analyze the effect of population density, educational access inequality, and health access inequality to economic growth in Indonesia. This research type is explanatory research by using quantitative method. The analysis technique used multiple regression analysis with dummy variable. The result of this study are obtained: 1) population density has a significant effect on economic growth; 2) Educational access inequality has a significant effect on economic growth; 3) Health access inequality has no significant effect on economic growth.